The Analysis of Adolescents Knowledge of Condom and Free Sex Behavior - Selvia Juwita Swari; Indah Muflihatin (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Teenagers are a group of young people in the transition from children to adulthood. At this particular period adolescents have experienced rapid physical and psychological development in which physically they are considered to be adults but psychologically immature. In terms of biological development, most teenagers are mature, but socially, mentally and emotionally still cannot be considered to be matured. Thus, such condition might trigger a variety of adolescent problems such as drug abuse, pre-marriage sex which will likely result in unexpected pregnancies and even illegal abortion. This study aims to identify and analyze adolescent knowledge of condoms and the incidence of free sex behavior. The research used cross sectional method with a sample of 70 people taken in total sampling. Data were analyzed with fisher exact. The results showed a significant correlation between knowledge and kissing and petting behavior with p value 0.02 <0.05. Yet, No relationship showed up between knowledge and necking behavior (p value of 0.13) and sexual intercourse (0.43) Based on the study results, schools are expected to cooperate with local health centers to provide counseling on adolescent reproductive health, especially on free sex behavior